ANALISIS ARAH KEBIJAKAN PEMERINTAH TERHADAP UNDANG-UNDANG SPPA DAN RUU NARKOTIKA DALAM MEWUJUDKAN PERLINDUNGAN DAN KEPENTINGAN TERBAIK BAGI ANAK - Noman Tuboinam Waruwu; Agusmidah (Case Law : Journal of Law, 2026)
Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (UU SPPA) establishes restorative legal policy, prioritizing diversion and the Best Interests of Children. However, this policy direction has the potential to be disharmonious with the Draft Narcotics Law (RUU Narcotics), which tends to maintain repressive criminal provisions and minimum sanctions, thus creating a dilemma of normative inconsistency. This study aims to analyze the consistency of the government's legal policy between the SPPA Law and the Narcotics Bill, and to reconstruct optimal policies to guarantee protection and the Best Interests of Children. This study uses a normative legal method with a statutory approach and a conceptual approach. Data are analyzed qualitatively through legal interpretation and construction of the SPPA Law and the draft Narcotics Bill. The results of the study indicate policy inconsistencies because the severe criminal provisions in the Narcotics Bill have the potential to undermine the obligation to diversion and limit judicial discretion. The minimum criminal sanctions maintained in the bill contradict the restorative spirit of the SPPA Law. The conclusion of this study is that the SPPA Law has not been fully internalized in the Narcotics Bill. The research recommends that the Narcotics Bill be reconstructed by incorporating the SPPA Law clause as an absolute lex specialis, removing the minimum sentence provisions for children, and requiring an Integrated Assessment as a prerequisite for determining a child's legal status to ensure the protection and best interests of children. Keywords: Policy Direction, SPPA Law, Narcotics Bill, Child Protection, Best Interests of the Child.